2019
DOI: 10.1021/acs.biomac.8b01577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Antibacterial Glycosylated Polycaprolactones Bearing Imidazoliums with Reduced Hemolytic Activity

Abstract: Most synthetic antimicrobial polymers are not biodegradable, thus limiting their potential for large-scale applications in personal care disinfection and environmental contaminations. Poly(εcaprolactone) (PCL) is known to be both biodegradable and biocompatible, thus representing an ideal candidate biopolymer for antimicrobial applications. Here we successfully grafted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…However, the toxicity toward host mammalian cells is not always as low as desired, in particular in polymers with high hydrophobic contents [15]. Attempts to improve the biocompatibility of antimicrobial polymers include the incorporation of non-ionic and biocompatible moieties such as polyethylene glycol (PEG) [16][17][18][19] and glycopolymers [20,21]. The toxicity of cationic amphiphilic polymers is typically evaluated by the hemolytic activity towards mammalian red blood cells (RBCs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the toxicity toward host mammalian cells is not always as low as desired, in particular in polymers with high hydrophobic contents [15]. Attempts to improve the biocompatibility of antimicrobial polymers include the incorporation of non-ionic and biocompatible moieties such as polyethylene glycol (PEG) [16][17][18][19] and glycopolymers [20,21]. The toxicity of cationic amphiphilic polymers is typically evaluated by the hemolytic activity towards mammalian red blood cells (RBCs).…”
Section: Introductionmentioning
confidence: 99%
“…Chan group polymerized with NCA and chitosan to simulate the peptidoglycan component of the bacterial cell wall (Li et al, 2012;Hou et al, 2017). On these bases, they designed a variety of glycosylated cationic chitosan-based polymers, whose antibacterial activity and selectivity can be adjusted to meet application requirements through changing the glycosyl composition and cationic residues (Pranantyo et al, 2017;Xu et al, 2019). For example, glucosamine-functionalized star polymers (S-GSA 25) showed high bactericidal activity against Gram-positive bacteria while maintained good biocompatibility (Wong et al, 2016).…”
Section: Cationic Polymersmentioning
confidence: 99%
“…[ 5 ] Recently, our group have also developed a series of polycaprolactone (PCL) based glycopolymers exhibiting good potency against bacteria, including drug resistant strains. [ 6 ] Apart from degradability, the biocompatibility of glycosides in the polymers has also been systematically studied (Figure 1). A library of glycosylated PCLs has been prepared with different sugar moieties in various ratios through copper catalyzed click chemistry, and the results showed that the biological profile could be significantly improved by incorporating carbohydrates.…”
Section: Biocompatibility Of Carbohydratesmentioning
confidence: 99%